(untitled)
We prove sharp Lorentz-and Morrey-space estimates for the gradient of solutions u to nonlinear parabolic equations of the type ut div a(z;Du) = g; on T = (T; 0); where the vector field a is assumed to satisfy classical growth and ellipticity conditions and where the inhomogeneity g is only assumed to be integrable to some power > 1. In particular we investigate the case where stays below the exponent allowing for weak solutions u 2 L2(T; 0;W1;2( )). Our results extend for p = 2 the results for elliptic equations [48] to parabolic equations. © 2012 University of Houston., author = Habermann, Jens and Baroni, Paolo, faupublication = yes, journal = Houston Journal of Mathematics, keywords = Calderon-Zygmund estimates; Morrey-Lorentz regularity; Parabolic equations, note = UnivIS-Import:2015-03-09:Pub.2012.nat.dma.lma2.newgra, pages = 855-914, peerreviewed = Yes, title = New gradient estimates for parabolic equations, volume = 38, year = 2012